Effect of Cosmetic Procedures in the Periorbital Area on the Organ of Vision: Overview - V. N. Trubilin; E. G. Poluninа; V. V. Kurenkov; D. V. Andzhelova; S. G. Kapkova; K. V. Chinenova (Oftalʹmologiâ, 2018)
Practitioners in ophthalmology in recent years often face the effects of cosmetic procedures on the paraorbital area, as well as directly on the eyelids. Such influences include botox injections in paraorbital area, blepharoplasty, eyelash extensions, injections of various fillers, etc. These manipulations are widely used and often lead to various complications of the vision organ. Eyelash extensions are a popular procedure, especially among urban, young women, but there are potential health risks from the procedure. Tattooing of eyelids leads is the cause of dysfunction of meibomian glands, which can lead to the dry eye syndrome, manifested as complaints about a feeling of chronic discomfort in the eyes. Due to the growing popularity of the age tattoo, it is necessary to pay close attention to the training of specialists who conduct this procedure. The procedure for permanent eyelid make-up should be performed after careful consideration of possible complications, and by special trained professionals. In recent years, various cosmetic procedures for rejuvenating the face plays great role, for example, injections of botulinum toxin, as well as various dermal fillers — the application of which is aimed at eliminating the aging signs. The qualification of the specialist his awareness of the occurrence of possible complications, as well as the awareness of patients who undergo this procedure is an important aspect in the application of botulinum toxin, both for therapeutic and cosmetic purposes. Of great interest are the complications associated with ischemia in the form of soft tissue necrosis and vascular occlusion caused by fillers introduction. It is reported that the frequency of vascular occlusion with dermal fillers is up to 3 per 1000 injections. The only proven elimination of soft tissue ischemia in case of a hyaluronic acid filler use is early high-dose hyaluronidase injections, since this drug helps deactivate the action of hyaluronic acid. Modern ophthalmologic practice is inextricably linked with the latest methods of modern cosmetology medicine, the results of it can effect on the functions of the whole organism as the organ of vision in particular. This fact and the specificity of possible complications arising from cosmetic procedures in the periorbital zone should be taken into account during the anamnesis collecting anamnesis, and examining patients, including preoperative preparation, and in choosing the treatment method.